Fake news como ferramenta persuasiva de desinformação na era da pós-verdade - Schumacher, Matheus Vinícius (My University, 2020)
The present academic work studies the fake news through the communicative and persuasive bias, as well as its insertion in the post-truth context. It aims to identify how fake news persuades with false information in the post-truth era. For this, the hypodermic needle model, persuasion theory, the types of fake news and the concepts of advertising were labored, considering authors such as Mauro Wolf (1987), Tandoc, Lim and Ling (2017) and Neusa Demartini Gomes (2001). Through the descriptive study, this work will approach qualitative research in the case study through the source of evidence of the documentation in three publications found on the social networks Facebook by Fernanda Barth, Twitter by the Special Secretariat for Social Communication of the Presidency of the Republic of Brazil and a anonymous WhatsApp posting. It was concluded that fake news persuades when it presents false information that meets the needs of the ideological values of the public reached by the message. [resumo fornecido pelo autor]
Este trabalho estuda as fake news pelo viés comunicativo e persuasivo, tal como sua inserção no contexto de pós-verdade. Objetiva identificar como as fake news persuadem com informações falsas na era da pós-verdade. Para isso, foram trabalhadas a teoria hipodérmica, abordagem empírico-experimental ou teoria da persuasão, os tipos de fake news e os conceitos de propaganda, considerando autores como Mauro Wolf (1987), Tandoc, Lim e Ling (2017) e Neusa Demartini Gomes (2001). Através do estudo descritivo, este trabalho terá como abordagem a pesquisa qualitativa no estudo de caso por meio da fonte de evidência da documentação em três publicações encontradas nas redes sociais Facebook de Fernanda Barth, Twitter da Secretaria Especial de Comunicação Social da Presidência da República e uma publicação anônima de WhatsApp. Concluiu-se que as fake news persuadem quando apresentam a informações falsas que satisfazem as necessidades dos valores ideológicos do público atingido pela mensagem. [resumo fornecido pelo autor]
Keywords: Publicidade; Fake news; Redes sociais on-line; Propaganda; Comunicação